Fabrication and characterization of multilayer waveguide for integrated optics - SHARMA, SUDHIR KUMAR (2002)
We report on our systematic and detailed study of fabrication and characterization of polyaniline (PA) prepared by vacuum deposition and polystyrene (PS) prepared by dip coating method thin film optical waveguides. The four-layer consisting of substrate (glass) /PA/PS/air has been used for demonstrating polarization filter action.